ANALISIS PENETAPAN PENGADILAN NEGERI LUBUKLINGGAU NOMOR 3/PDT.P/2015/PN LLG. TENTANG PERKAWINAN BEDA AGAMA - DELIAN ADLOFENO; Sahruddin Sahruddin (Private Law, 2023)
This study aims to analyze the validity and rationale of the Lubuklinggau District Court Number 3/Pdt.P/Lig, regarding interfaith marriage in giving determination. This research method uses a descriptive legality normative approach. The data type used consists of primary data, namely laws and regulations and secondary data derived from books or scientific papers related to this research. The data collection method uses library data, which is analyzed descriptively-deductively. The first study’s results indicate that interfaith marriages in Indonesia are not permitted because they do not meet the formal requirements for a marriage to be valid. Second, regarding the basis for the judge's consideration, it has fulfilled the juridical, sociological and philosophical aspects. However, in the philosophical aspect, the judge did not consider speculatively. This means speculative considering what this means is the legal consequences that occur when the stipulation is given.